The mechanistic study of the convesion of greenhouse gases (C02 and 802) into useful products using novel heterogeneous catlysts from rice husk under mild conditions. - Adam, Farook (Universiti Sains Malaysia, 2015)
Four catalysts, viz. MCM-41-lmi/Br, RHAPrS03H, RHAPrTMG and RHAPrTBD were synthesized and fully characterized. All catalysts were investigated with respect to CO2 conversion. Good catalytic activity were shown by all the catalysts under mild reaction contidions.